(untitled) - Barnes, John A. (New York, NY., 2005)
Whether in business, politics, or the community, today's leaders have more in common with their legendary predecessors than they may realize. Intensely scrutinized by their constituents, colleagues, the media, and the public, leaders make decisions that affect lives far beyond their immediate surroundings. Perhaps no figure in recent memory more fully personifies leadership than President John F. Kennedy. Leading the nation in a time of unprecedented turbulence, challenge, and opportunity, Kennedy led his administration (and the country) with a courage and determination that even his harshest critics respected.
Keywords: Leaderships,Communication in management,Teams in the workplace,Decision making,Crisis management,Kennedy, John Fitzgerald 1917 - 1963; Case studies,Case studies,Case studies,Case studies,Case studies